(untitled) (Revista Tempo e Argumento, 2014)
This article investigates the uses of the Internet made by fascist groups from Brazil and Argentina. We use as main sources professedly fascist websites created shortly after the popularization of the Internet. From the perspective offered by the comparative methodology advocated by Marc Bloch, the text examines the relation between Brazilian homepages and the best known South American far-right website, Ciudad Libertad Opinión, created in 1999 with the primary purpose of spreading fascist ideas and providing support to other extremist groups. We point out the strategic role played by the web portal Libre Opinión as articulator between fascist groups in South America, this is a key contributor in the diffusion of Brazilian web pages marked to convey on a regular basis xenophobic, racist, anti-Semitic, and homophobic messages. Keywords: Fascism – Brazil; Fascism – Argentina; Internet; South America